An empirical study of the influence of culture on talent acquisition and relationship with organisational global ambitions in Indian organisations - Liu, Yi; Pearson, Cecil (Springer, 2015)
Work organisations around the world are experiencing transformations in a range of people management practices when encountering intercultural forces of the global market based economy. In particular, the process of talent acquisition, which is recognised as a critical component of competitive advantage, has shifted significantly from traditional arrangements. Contemporary Indian organisations are not immune from globalisation influences and many have adopted a hybridisation perspective that blends with international management knowledge and historical indigenous nuances. The extent of hybridisation in 72 Indian organisations was investigated with a pluralist study design. Results of the quantitative analyses, that demonstrated national culture influenced the relationships between talent acquisition and dimensions of corporate global ambition, were confirmed with qualitative assessments. Implications and consequences are outlined.